Knowledge of the knowledge of the experience and the construction of teacher's poetic art education - Valentim Portela, Maria Brigida; Santos, Genivaldo de Souza [UNESP]; Abou Gebran, Raimunda (Univ Metodista Piracicaba-unimep, 2016)
This article synthesizes the ideas developed in the masters research entitled the locus of experience in construction of teaching poetry to art education and aims to reflect on the impact of knowledge of experience in the construction of teaching poetry to art education in contemporary times. Specifically, the concept of we question the concept of experience, which in contemporary philosophy was valued and incorporated keynote object in the research of philosophy of education, by its importance no development of sensitive educational practices, who value personal expression, the uniqueness, diversity and transculturation, which can be herself possibility, creation, invention, event, poetic. We refer our thoughts especially in Larrosa (2014), Pagni and Gelamo (2010), Barbosa (2006, 2010), Aguirre (2009), Masschelein (2008). The present research is methodologically in the survey and bibliographical analysis, in the context of a qualitative approach. Consider, by way of conclusion, that the knowledge of experience can enhance the human dimension of education in favor of a creative teacher, and ethics.
Keywords: EXPERIENCE; EDUCATION; ART